Development measurement in Nepal using population census 2021 data - Sapkota, Bhesh Nath (Rural Development Journal, 2025)
The development measurement in Nepal using Population Census data 2021 yield Human Development Index (HDI) value 0.7094, Gender related Development Index (GDI) 0.7087 and Gender Empowerment Measures (GEM) 0.5581. The HDI, GDI and GEM value of Nepal lies medium level countries range. The HDI value is Nepal has increased 0.463 to 0.7094 from 1999 to 2021 about 24 years period with change in number 0.246. Similarly the GDI value has increased from 0.441 to 0.7087 with change in number 0.267. Similarly the GEM number has increased around 0.358.